1985
DOI: 10.1080/09670878509370983
|View full text |Cite
|
Sign up to set email alerts
|

Species quantification and seasonal abundance of ticks (Acarina: Ixodidae) in the eastern province of Zambia: Ticks from cattle

Abstract: Ticks from cattle were collected for the purposes of quantifying the number of tick species and their relative abundance at Msekera Regional Research Station. Fifteen species were recorded. It was found that although different species of ticks parasitized cattle throughout the year, their peaks of abundance were dependent on the season. The majority of the species had their peaks during the wet season (November to April). Rhipicephalus punctatus (Warburton) was found to be the most abundant species followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…In agreement with our data, Mulilo (1985) found that during a heavy rainfall year in Zambia the number of R. appendiculatus adults on cattle increased while there was a corresponding decrease in the number of B. microplus (congener of B. decoloratus). No correlation was found between the abundance of this species and monthly rainfall.…”
Section: Boophilus Decoloratussupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with our data, Mulilo (1985) found that during a heavy rainfall year in Zambia the number of R. appendiculatus adults on cattle increased while there was a corresponding decrease in the number of B. microplus (congener of B. decoloratus). No correlation was found between the abundance of this species and monthly rainfall.…”
Section: Boophilus Decoloratussupporting
confidence: 92%
“…Field studies have shown a distinct seasonal activity pattern for R. appendiculatus adults, with the number of ticks on host animals increasing markedly with the onset of the rains, remaining high throughout the wet season, and decreasing to very low levels during the dry season (Kaiser et at., 1991;McCulloch et al, 1968;Minshull and Norval, 1982;Mulilo, 1985;Pegram et al, 1986;Rechav, 1982;Short and Norval, 1981 a;Smith, 1969;Wilson, 1946). In the wet season, adults were more abundant during 1991 than during the drought year of 1992, whereas there was no difference between years for the larvae or nymphs.…”
Section: Rhipicephalus Appendiculatusmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to obtaining nutritional benefits, oxpeckers use their hosts as mobile perches and sources of nesting material. Ungulates, in turn, reap the benefits of ectoparasite removal by associated oxpeckers, which includes the prevention of blood loss, appetite suppression, tick toxicosis, and skin, bacterial and protozoan diseases (Little, ; O'kelly & Seifert, ; Seebeck, Spingell & O'kelly, ; Williams, Hair & Mcnew, ; Price, ; Mulilo, ; Norval et al ., ; Hart, Hart & Mooring, ; Oorebeek & Kleindorfer, ). Because of this cleaning behaviour, the oxpecker–ungulate interaction is generally categorized as mutualistic, an interspecific interaction in which each species receives a net benefit (Bronstein, ,b, , ; Holland & Deangelis, ).…”
Section: Introductionmentioning
confidence: 99%
“…shown (Biguezoton, 2016;Fantahun, 2012;Farougou, 2006Farougou, , 2007Keesing et al, 2018;Mattioli et al, 1997;Mulilo, 1985). This pattern is most characteristic for two or three-host tick species (Amblyomma spp.…”
Section: Knowledge Of Herders On Cattle Tick Seasonalitymentioning
confidence: 96%